Contesting views on mobility restrictions in urban green spaces amid COVID-19—Insights from Twitter in Latin America and Spain. (January 2023) - Sainz-Santamaria, Jaime; Moctezuma, Daniela; Martinez-Cruz, Adan L.; Téllez, Eric S.; Graff, Mario; Miranda-Jiménez, Sabino
Abstract: Positive sentiments towards urban green spaces (UGS) unequivocally increased worldwide amid COVID-19. In contrast, this paper documents that views on mobility restrictions applicable to UGS are of a contested nature. That is, while residents unambiguously report positive sentiments towards UGS, they do not share views on how to administer access to UGS—which is a matter of public policy. These contesting views reflect opposite demands that managers of UGS had to balance during the pandemic as they faced the challenge of reducing risk of spread while providing services that support physical and mental health of residents. The empirical analysis in this paper relies on views inferred through a text classification algorithm implemented on Twitter messages posted from January to October 2020, by urban residents in three Latin American countries—Argentina, Colombia, and Mexico—and Spain. The focus on Latin America is motivated by the documented lack of compliance with mobility restrictions; Spain works as a comparison point to learn differences with respect to other regions. Understanding and following in real-time the evolution of contesting views amid a pandemic is useful for managers and city planners to inform adaptation measures—e.g. communication strategies can be tailored to residents with specific views. Highlights: Amid COVID-19, social media showcased contesting views on mobility restrictions applicable to UGS. Contesting views on regulation of access hold together with unambiguous increase in positive sentiments towards UGS. These views reflect residents' stands with respect to how UGS should be used during a pandemic event. Social media provides unstructured information to design and communicate adaptation measures in real-time.